Production Risk Mitigation Strategies In Small-Scale Goat Milk Industries - Nurul Risti Mutiarasari; Deana Feraya Azzahra; Yogi Nirwanto; Leny Yuliyani; Ery Supriyadi Rustidja (International Journal of Business and Quality Research, 2026)
The purpose of this research is to identify the causes and impacts of production risks and develop appropriate mitigation strategies to deal with risks at Abah Farm dairy goat farm. The data analysis design used is the House of Risk (HOR) analysis. The results of the study showed that the causes and impacts of goat milk production risks consist of the process of doe/nanny rearing, the milking process, and the packaging and distribution process. Risk mapping of goat milk production in the rearing process five activities cause the risk of goat milk production, including feeding activities, animal sanitation, cage sanitation, livestock reproduction, and livestock animal health. Furthermore, in milking goat milk, five activities are causes, namely the milking place (cage), determining the intensity and time of milking, milking preparation, the way during the milking process, and the completion of milking. In the completion and packaging of milk, two activities are caused, namely the handover stage and the goat milk packaging stage. Several mitigation strategies can be carried out, including in the process of raising mothers, the main priority of the mitigation strategy is to adjust the composition of high-protein green feed. Furthermore, in the milking process, the top priority mitigation strategy is to supervise the implementation of the goat milking standard procedure by the supervisor and in the milk packaging and distribution process, the top priority mitigation strategy is to back up goat milk production data in a separate notebook or soft file data storage on a computer or email.